Modificações geomórficas nos estilos fluviais da bacia do alto curso do Rio Piranhas, semiárido paraibano - Rodrigues, Jeferson Mauricio (2021)
Dry lands are generally characterized by being areas of little rain, however, the details of their surface are attributed to the performance of river systems. Therefore, understanding dry land landscapes means understanding river processes and forms. However, dry land rivers have a different behavior from wetland channels, considering the irregular rainfall variability. Ephemeral and intermittent flows are predominant and the way these channels modify their morphology and processes over time is also inherent to the environmental dynamics of dry lands. This study took place in the hydrographic basin of the upper Piranhas River, located in the Paraiba hinterland (semi-arid environment), where this basin will function as a receiver of the waters of the São Francisco River when the North Axis is completed. This research aimed to analyze the river dynamics and the propensity to change channels. For that, it was necessary to analyze the physical characteristics of the basin, define the river styles, their respective patterns of propensity to change and geomorphic conditions. The methodology used was the theoretical-methodological proposal of river styles, considering the first 2 stages of this approach, which allowed to analyze the current and past river characteristics of the stretches identified. In this perspective, 8 river styles were identified, ranging from confined and partially confined to non-confined. In general, the confined styles were related to the areas closest to the head and presented rocky control on the margins and beds with high flow energy, giving them low levels of sensitivity and good geomorphic condition. Among the partially confined styles, the predominance was of channels with moderate sensitivity, where only EFPCRA showed a high propensity to change according to its geo-indicators and poor geomorphic condition, as it is an unexpected stretch for its position in the hydrographic basin. The untrusted styles had a predominance of high sensitivity in their stretches, where only the EFNCRC located near the mouth of the Piranhas River presented moderate sensitivity, in view of its rocky control in the bed, however, its poor geomorphic condition was associated with its unexpected characteristics for their position in the watershed. Finally, the historical analysis of the flow allowed to have an understanding about the dynamics of the styles that showed greater propensity to change, evidencing the possible events of high magnitude that generated morphological alteration in these styles.